Psychometric properties of the ASQ–3 in a nationally representative sample of Uruguay. (June 2021) - Alvarez-Nuñez, Lucía; González, Meliza; Rudnitzky, Fanny; Vásquez-Echeverría, Alejandro
Abstract: Background: The Ages & Stages Questionnaires Third Version (ASQ-3) identifies the risk of developmental delay in children aged 2 to 66 months. The ASQ-3 is available in many languages. However, there is little evidence of the psychometric properties of the Spanish version and using nationally-representative samples. Aims: This study evaluates the reliability and factor solution of the Spanish version of the ASQ-3 (18- to 54-month questionnaires) in a large, representative sample of Uruguayan children. Besides, it explores the association of ASQ-3 scores with sociodemographic characteristics. Method: Participants were 4016 main caregivers selected randomly across the country who completed the ASQ-3 for their children. All participants responded to the ASQ-3 and a sociodemographic questionnaire within the context of a government-run survey of child development. Results: Most versions of the ASQ-3 in Spanish have acceptable-to-good psychometric properties, supporting the 5-factor-solution. Personal-Social and, to a lesser extent, Problem-solving scores were the subscales that showed more suboptimal internal consistency coefficients. Scores showed higher ceiling effects than the original US sample but varied across domains, with Gross Motor showing the highest pattern. Sex and socioeconomic status are associated with scores of most age-versions and subscales of the ASQ-3. Conclusions: In general, results support the reliability and dimensionality of ASQ-3 scores, but psychometric properties varied across age-version and domains. Overall, earlier versions presented less precision, while the Personal-social domain showed reduced reliability in most age-versions. Highlights: The ASQ-3 identifies the developmental delay risk in children from 2 to 66 months. We analyze the psychometric properties of the ASQ-3 in Spanish using a nationally representative sample. Questionnaires from 33 months to 54 months provide reliable and valid scores for key developmental areas. Results in this Uruguayan sample showed higher ceiling effects than the original sample used for norm-reference Personal-social subscale presented reduced psychometric precision in most versions.